2016
DOI: 10.1002/aur.1688
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of urine indolylacroylglycine is not useful in the diagnosis or dietary management of autism

Abstract: Lay AbstractIncreased urinary excretion of indolylacroylglycine (IAG) has been proposed as a useful biomarker for the diagnosis and dietary management of patients with autism spectrum disorder (ASD). It has been suggested that this may be due to abnormal metabolism of tryptophan and/or evidence of increased gut permeability to peptides, and may be a valuable biomarker of a process underlying autism viz. the hypothesis that ASD could be caused by increased gut absorption of neuroactive peptides, derived from gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…IAcrGly is one of the physiological components in urine. It was hypothesized that abnormal gut flora could promote the conversion of tryptophan to indolyl propionic acid, which could cause an increased IAcrGly level in urine 58 , 59 . The trans-verse situation might be true for patients with bladder or CRC.…”
Section: Discussionmentioning
confidence: 99%
“…IAcrGly is one of the physiological components in urine. It was hypothesized that abnormal gut flora could promote the conversion of tryptophan to indolyl propionic acid, which could cause an increased IAcrGly level in urine 58 , 59 . The trans-verse situation might be true for patients with bladder or CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that anti-inflammatory 13-oxoODE can inhibit the secretion of TNF-α by macrophages stimulated by EC, and this process can be reversed by PPARγ antagonist GW9662 (Ryman et al, 2016;Wysoczanski et al, 2019). While urinary indolylacroylglycine levels are elevated in ASD children, inconsistent results have been reported elsewhere in the literature (Dalton et al, 2017). The reduction of Bacteroidetes may weaken the immune tolerance of intestinal microbe (Jalanka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%